Influence of Self Efficacy on Graduate Performance in the Public Sector Organizations: Moderated Mediation Analysis with Economic Crisis and Job Satisfaction - Priyadharsan, S.; Saravanabawan, A. (University of Kelaniya, 2022)
In the current scenario of Sri Lanka, the economic crisis plays a major role. In line with this, people feel fear and anxiety are common to all, and this psychological issue impacts their physical and mental health. Consider self-efficacy indicated that people believe they can have the abilities and capabilities to complete the given task successfully. High self- efficacy of people easily handle unexpected sudden events in work and family life. Especially the self-efficacy of people satisfied with their job and contribute to performance as well. Looking into the problem statement, graduate employees’ attitude is highly influenced to choose a government job in Sri Lanka. Even though they face challenges are a mismatch of skills in the labor market and difficulty in absorbing suitable jobs. Further, previous studies have tested self-efficacy and job performance in different areas, which show positive, negative, and no relationship with these variables. A dearth of areas of research conducted in the Sri Lankan context. The main objective of the research are to assess the co-relationship and impact between self-efficacy and job performance, to recognize the mediating effect of job satisfaction between self-efficacy and job performance, and to find out the moderating effect of economic crisis between self-efficacy and job satisfaction. Conceptual variables are self-efficacy, job satisfaction, economic crisis, and job performance. Thousand four hundred and fourteen samples were selected from the Eastern Provincial Council on the basis of a stratified propionate sampling method.
Keywords: Self Efficacy; Job Satisfaction; Job Performance; Economic Crisis